From Riau to Singapore: A content analysis of the Rushdiah club’s major published writings (ca. 1890-1950) - Zakariya, Hafiz; Oktasari, Wiwin (UTM Press and Faculty of Islamic Civilization, UTM, 2017)
This study examines the prominent Malay literary organization in the Sultanate of Riau-Lingga: Rushdiah Club’s writing and printing activities. It provides a descriptive content analysis of books on various subjects that were published by the printing presses under the auspices of the members of the Rushdiah Club in Riau, Singapore and Penang from 1893 to 1950. Specifically, these presses were Matba‘at al-Ahmadiyyah and Matba‘ah al-Riyawiyyah in Riau-Lingga; Matba‘at al-Ahmadiyyah (better known as the Ahmadiah Press) and al-Imam Printing Company Ltd. in Singapore; and Jelutong Press in Penang. The objective of this paper is to discuss the roles of the Rushdiah Club, particularly its contribution to the Malay societies by flourishing the writing and printing culture. Furthermore, this paper investigates how their publications had constructed a specific pattern of Islamic thought and culture as the members joined intellectual debates over the issue of Islamic reformism. The analysis of the catalogues involves two phases: firstly, examining the writers; secondly, itemizing them according to categories, content, and characteristics of the books. The finding of the study indicated that the most common theme is Islam and religion, which is about 73 books (36.86%). This study also contends that the Rushdiah Club which was strongly anchored by the Islamic ethos, responded to colonialism through non-violent means.